2020
DOI: 10.1371/journal.pntd.0008961
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 vaccine demand and hesitancy: A nationwide online survey in China

Abstract: Background This study attempts to understand coronavirus disease 2019 (COVID-19) vaccine demand and hesitancy by assessing the public’s vaccination intention and willingness-to-pay (WTP). Confidence in COVID-19 vaccines produced in China and preference for domestically-made or foreign-made vaccines was also investigated. Methods A nationwide cross-sectional, self-administered online survey was conducted on 1–19 May 2020. The health belief model (HBM) was used as a theoretical framework for understanding COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

80
590
18
24

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(712 citation statements)
references
References 26 publications
80
590
18
24
Order By: Relevance
“…Income had no influence on COVID-19 VWR in the paid vaccine model, but the low-income group had a higher COVID-19 VWR than the high-income group in the free vaccine model (86.2% vs. 78.97%, OR = 1.536), which was different from previous research [5,6,[22][23][24][25]. The VWR growth rate of free vaccinations for the low-income group was 17.37% (from 73.44% to 86.2%), but that for the high-income group was only 6.64% (from 74.05% to 78.97%).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Income had no influence on COVID-19 VWR in the paid vaccine model, but the low-income group had a higher COVID-19 VWR than the high-income group in the free vaccine model (86.2% vs. 78.97%, OR = 1.536), which was different from previous research [5,6,[22][23][24][25]. The VWR growth rate of free vaccinations for the low-income group was 17.37% (from 73.44% to 86.2%), but that for the high-income group was only 6.64% (from 74.05% to 78.97%).…”
Section: Discussioncontrasting
confidence: 97%
“…Previous vaccination studies have shown that many factors are responsible for the COVID-19 vaccination willingness rate (VWR), such as socio-economic factors, awareness of the severity and susceptibility to the disease and trust in the vaccine [4][5][6][7][8]. From a survey in Japan, Yoda and Katsuyama found that males, older age people, rural residents and chronic disease sufferers displayed the highest willingness toward COVID-19 vaccination [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes more than 90% acceptance rates in Indonesia, Malaysia and one study from China [51,52,59]. Another two surveys on the general public in China reported vaccine acceptance rates of more than 80%, with an additional survey in South Korea that reported a rate of 79.8% [46,63]. A later survey from Shenzhen, China, by Zhang et al, which surveyed parents/guardians who were factory workers, on their acceptability of children COVID-19 vaccination reported a lower rate of 72.5% compared to previous studies [71].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the MoVac-COVID19S can be used to explore and understand why a population reports lower levels of motivation to get vaccinated. Although many studies have reported the high willingness of COVID-19 vaccinating uptake [e.g., 21,[35][36][37][38], low acceptance can still be observed [39][40][41]. Therefore, with the use of MoVac-COVID19S, healthcare providers and researchers can obtain in-depth information regarding the underlying mechanism of individuals who are unwilling to get vaccinated.…”
Section: Discussionmentioning
confidence: 99%